BASIC EDUCATION MUSIC TEACHER AND PRIVATE MUSIC TEACHER: A REFLECTION ON THEIR ATTRIBUTIONS AND REMUNERATION IN BRAZIL IN 2024 - da Silva, Giácomo de Carli (Seven Editora, 2024)
The present research was based on the methodology of research via the internet. As an objective, it aimed to expose a small analysis of the remuneration and attributions of Music teachers, comparing the Music teacher of Basic Education with the autonomous/extra-class Music teacher, giving more emphasis to the scenario of the latter. Thus, the following questions were prepared to be answered by this author who has in his curriculum as a teacher in Music the school curriculum of Basic Education, and also, has experience in teaching practice as an autonomous Music through MEI (Individual Microentrepreneur): Which teacher has more attributions in his work as a music teacher? Which of these earns the most per hour of work? As a result, the investigation brought that clearly, the Music teacher of Basic Education is the one who has the most attributions, given the number of students per class that he attends at once, in addition to having to deal with the lack of work material and adequate space for Music classes. And in response to the second question, the survey pointed out that it is the private music teacher who has the best remuneration per hour of work, disregarding, of course, the benefits guaranteed by law to Basic Education teachers, such as planning hours. DOI:https://doi.org/10.56238/sevened2024.037-015